3‐D seismic tomography of the lithosphere and its geodynamic implications beneath the northeast India region. Issue 5 (25th May 2017) - Raoof, J.; Mukhopadhyay, S.; Koulakov, I.; Kayal, J. R.
Abstract: We have evolved 3‐D seismic velocity structures in northeast India region and its adjoining areas to understand the geodynamic processes of Indian lithosphere that gently underthrusts under the Himalayas and steeply subducts below the Indo‐Burma Ranges. The region is tectonically buttressed between the Himalayan arc to the north and the Indo‐Burmese arc to the east. The tomographic image shows heterogeneous structure of lithosphere depicting different tectonic blocks. Though our results are limited to shallower depth (0–90 km), it matches well with the deeper continuation of lithospheric structure obtained in an earlier study. We observe low‐velocity structure all along the Eastern Himalayas down to 70 km depth, which may be attributed to deeper roots/thicker crust developed by underthrusting of Indian plate. Parallel to this low‐velocity zone lies a high‐velocity zone in foredeep region, represents the Indian lithosphere. The underthrusting Indian lithosphere under the Himalayas as well as below the Indo‐Burma Ranges is well reflected as a high‐velocity dipping structure. The buckled up part of bending Indian plate in study region, the Shillong Plateau‐Mikir Hills tectonic block, is marked as a high‐velocity structure at shallower depth. The Eastern Himalayan Syntaxis, tectonic block where the two arcs meet, is identified as a high‐velocity structure. The Bengal Basin, tectonic block to the south of Shillong Plateau, shows low velocity due to its thicker sediments. Based on the tomographic image, a schematic model is presented to elucidate the structure and geodynamics of Indian lithosphere in study region. Key Points: The Indian lithosphere is imaged as a high‐velocity body that gently underthrusts below the Himalayas and subducts below the Indo-Burma Ranges down to 600 km depth Below the Northeast India region, the Indian lithosphere is buckled up, leading to high seismic activity Below the Indo‐Burma Ranges, downgoing part of the Indian slab is detached from the buckled up part and it is sinking at a steep angle